# Question #70e44

##### 1 Answer

Apr 16, 2017

#### Answer:

#### Explanation:

**Case #1#: the absolute value is positive**

#3m = m^2 - 10#

#0 = m^2 - 3m - 10#

#0 = (m - 5)(m + 2)#

#m = 5 or -2#

**Case #2#: the absolute value is negative**

#3m = -(m^2 - 10)#

#3m = -m^2 +10#

#m^2 + 3m - 10 = 0#

#(m + 5)(m - 2) = 0#

#m = -5 or 2#

However, the negative solutions are extraneous because the left hand side would be negative while the right hand side would be positive (by the definition of

Hopefully this helps!